From Hinengaro to Hineora: Tracing the origins of Intergenerational Trauma to attain Intergenerational Healing - Haami D; Tassell-Matamua N; Pomare P; Lindsay N (Elsevier Inc., 2024)
In Aotearoa New Zealand, colonisation continues to impact Indigenous Māori lived realities. However, Māori have been steadily progressing towards reclamation of all that was suppressed during colonisation, including tūpuna (ancestor) understandings of trauma and healing, of which wairua (referring to spirit) is at the centre. My research aimed to understand the role of wairua in the intergenerational transmission of trauma and healing through exploring my own lived experiences of trauma and healing. My methodology was developed based on tūpuna knowledge, resulting in the implementation of a Rongo-ā-Wairua Framework, a Whakapapa Methodological Approach, Whakapapa Wānanga and Te Pūtake: An Origin Analysis. Through this application of tūpuna knowledge and the centring of wairua within the research process, I uncovered the origins of the soul wounds I had inherited, enabling me to transform from Hinengaro, The Obscured Daughter into who I am now – Hineora, The Daughter of Healing.
Keywords: Indigenous knowledge; Intergenerational healing; Intergenerational trauma; Mātauranga Māori; Rongoā; Spirituality; Wairua; Whakapapa